TRADISI MENJAGA KESUCIAN PAKAIAN SHALAT: ETOS KEAGAMAAN DALAM KULTUR LIVING HADIS - Neny Muthiatul Awwaliyah (FiTUA: Jurnal Studi Islam, 2021)
This study examines the Tradition of Maintaining the Sanctity of Prayer Clothing This type of research is field research that uses a descriptive method of analysis, namely presenting data in accordance with the results of research obtained from research subjects in the field. Information and data obtained by jumping directly into the field in accordance with the subject of this research. its working instruments combine literature studies and field studies. This research also wants to see the Hadith that lives and responded by the popular community with the term Living Hadith. The reviewer did it to several students of UIN Sunan Kalijaga. The main focus of research is on the tradition of students in maintaining the sanctity of prayer clothes. This research involves sociological studies by borrowing Peter L. Berger's theory of social construction, namely internalization, externalization and objectivation.